Innovative Responses by Industry to Reduce Environmental Pollution and Degradation - Michieka , R. W.; Tirop , S. K. (African Journal of Education,Science and Technology (AJEST), 2013)
The growing environmental concerns, coupled with public pressure and stricter regulations, are changing the way of business across the world. Industry is on a three-stage journey from environmental compliance, through environmental risk management, to long-term sustainable strategies. Faced with the increasing burden of regulation, businesses choose to go beyond compliance towards comprehensive environmental programmes and sustainable development. To improve their control of environmental performance, companies conduct environmental health and safety (EHS) assessments, develop environmental policies and implement environmental management systems (EMS). Techniques such as pollution prevention and the 4Rs are used to translate policy objectives into practice. Operating costs are reduced through waste minimization, pollution prevention and the elimination of health and safety hazards. Whereas environmental protection is often regulated, sustainable development involves going beyond compliance. Most pollution is caused by human activities. There have been several innovative responses towards reduction of pollution in business and industry. These include pollution control; pollution prevention; waste minimization; use of energy alternatives and adoption of green economy; use of clean process technology and best management practices (BMPs); industrial ecology and polluter pays principle. Others include, greening public procurement, e-commerce and transactions. To counter negative environmental impacts, the final decade of the twentieth century saw a positive shift in emphasis from “end-of-pipe” controls on releases to the environment to the elimination of potential pollution at its source (“beginning of pipe”). Rather than try to “fix” a problem after it occurs, industries have began to “eliminate” the problem before it occurred.